1998
DOI: 10.1099/0022-1317-79-7-1801
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of helper T-cells generated from macaques infected with attenuated simian immunodeficiency virus.

Abstract: Deletion of the simian immunodeficiency virus (SIV)nef gene leads to an attenuated virus phenotype in vivo. We have previously shown that these viruses induce a potent cellular immune response in macaques. To extend these studies, we established virus-specific short-term T-cell lines from four rhesus macaques infected with a nef deletion mutant of SIV. These T-cell lines proliferated upon restimulation with whole SIV or SIV gp140 antigen in vitro. The proliferating cells were characterized as CD4 M helper T-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Nonetheless, studies have suggested that HIV-specific CD4 cells are important in the control of viremia in patients infected with HIV (Rosenberg et al 1997;Pitcher et al 1999;Kaufmann et al 2004;. As an extension, several groups have identified SIV-specific CD4 cells in various non-human primate models of SIV or SHIV infection (Mills et al 1991;Lekutis and Letvin 1997;Dittmer et al 1998;Kuroda et al 2000;Sarkar et al 2002). Within these analyses, one group examined MHC class II DRB restriction of the HIV envelope in a SHIV model (Lekutis and Letvin 1997;Kuroda et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, studies have suggested that HIV-specific CD4 cells are important in the control of viremia in patients infected with HIV (Rosenberg et al 1997;Pitcher et al 1999;Kaufmann et al 2004;. As an extension, several groups have identified SIV-specific CD4 cells in various non-human primate models of SIV or SHIV infection (Mills et al 1991;Lekutis and Letvin 1997;Dittmer et al 1998;Kuroda et al 2000;Sarkar et al 2002). Within these analyses, one group examined MHC class II DRB restriction of the HIV envelope in a SHIV model (Lekutis and Letvin 1997;Kuroda et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Dittmer et al (46) described a comprehensive analysis of Env SU-specific Th responses by using cultured short-term T cell lines from four monkeys inoculated with an attenuated SIV, while excluding comparative analysis of fine Th responses elicited to other SIV proteins. Thus, the current comparative analysis of the broadly reactive Th epitope peptides from SU and Gag showed that, despite similarity in protein lengths, SU contained only ϳ15% of the mapped broadly reactive Th epitope peptides, while Gag contained 40% of the epitopes.…”
Section: Discussionmentioning
confidence: 99%